FAKTOR-FAKTOR YANG MEMPENGARUHI VOLATILITAS HARGA SAHAM PADA PT WASKITA KARYA TBK - Harsi Romli; Meta Febrianti; Trie Sartika Pratiwi (Universitas Indo Global Mandiri)
The result of the study showed that partially there were two variables, namely trade volume and exchange rate that had positive and significant effect, in addition; it was found that the inflation had positive but not significant effect. While interest rate showed that there was a positive and significant effect on stock price. It could be seen from F-obtained 66.926 which was higher than F-table 2.59. It could be stated that independent variables affected the dependent variable. The predictive ability of the four variables on stock price volatility was indicated by the coefficient of determination (R2) 86.2%, while the remaining 45.4% which was affected by other factors not included in this study. Keywords : Stock Price Volatility, Trade Volume, Inflation, Exchange Rate and Interest Rate